Formulation and Evaluation of Herbal Tablets for the Treatment of PCOD using Kanchnar and Shatavari - Kalam, Sonali; Chaure, Rupali; Dapke, Poonam; Gorade, Sandip; Kale, Saurabh; Khore, Tushar; Sanap, Dr. Gajanan (Asian Journal of Pharmaceutical Research and Development, 2024)
Herbal tablets have been crucial in managing and preventing illnesses for centuries. Across cultures, herbs have advanced healthcare, leading to detailed herbal pharmacopeias. Integrating into mainstream healthcare, herbal tablets, especially Ayurvedic ones, are made from natural ingredients like Kanchanara and Shatavari, which are effective against Polycystic Ovary Disease (PCOD) by regulating cyst size and balancing hormones. Excipients in tablet formulations ensure correct dosage, integrity, and effective drug release. This underscores the growing importance of herbal medicine in modern healthcare. The meticulous selection of excipients, such as diluents, binders, disintegrants, and lubricants, is critical in the production of herbal tablets. Diluents add bulk to the tablet, binders ensure the tablet remains intact post-compression, disintegrants aid in the tablet's dissolution for effective drug release, and lubricants prevent sticking during manufacturing. Every excipient is selected based on its suitability and capacity to improve the tablet's characteristics, guaranteeing that the finished product is safe to eat and efficient. Moreover, the acceptability and widespread usage of herbal tablets demonstrate their potential to treat a variety of medical ailments. The ability of Shatavari and Kanchanara to treat PCOD, a condition marked by ovarian cysts and hormonal abnormalities, is evidence of the medicinal value of herbal medicine. Herbal pills are expected to become even more important in modern healthcare as research on the health benefits of various herbs continues, providing natural and holistic alternatives to traditional treatments.